2017
DOI: 10.1038/srep45512
|View full text |Cite
|
Sign up to set email alerts
|

Shock-Resistibility of MEMS-Based Inertial Microswitch under Reverse Directional Ultra-High g Acceleration for IoT Applications

Abstract: This paper presents a novel MEMS-based inertial microswitch design with multi-directional compact constraint structures for improving the shock-resistibility. Its shock-resistibility in the reverse-sensitive direction to ultra-high g acceleration (~hunderds of thousands) is simulated and analyzed. The dynamic response process indicates that in the designed inertial microswitch the proof mass weight G, the whole system’s stiffness k and the gap x2 between the proof mass and reverse constraint blocks have signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…The structure materials and substrates with high strength are used to prevent fracture failure and disengagement of bond wires. Xu et al [83] developed a multi-directional MEMS inertial switch with shock-resistance. It can resist ultra-high g acceleration (about 100,000 g) in the reverse sensitive direction.…”
Section: Passive Inertial Switchesmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure materials and substrates with high strength are used to prevent fracture failure and disengagement of bond wires. Xu et al [83] developed a multi-directional MEMS inertial switch with shock-resistance. It can resist ultra-high g acceleration (about 100,000 g) in the reverse sensitive direction.…”
Section: Passive Inertial Switchesmentioning
confidence: 99%
“…The tri-axial MEMS inertial switch with shock-resistibility (Xu 2016[83]): (a) the working principle; (b) the photo; (c) the schematic of the test circuit.…”
mentioning
confidence: 99%
“…In 2009, Jui-Chang Kuo et al proposed a passive inertial switch using multiwall carbon nanotube (MWCNT)–hydrogel composite integrated with an inductor/capacitor (L–C), and indicated that the inertial switches can be used for safety and protection in airbags, crash recorders, and arming and firing systems [ 4 ]. In 2017, Xu Q et al reported an Inertial Microswitch under Reverse Directional Ultra-High g Acceleration for IoT Applications [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Especially in recent years with the rapid development of the Internet of Things, the MEMS inertial switch has been more widely used. For example, a longitudinally driven inertial switch was proposed for IoT applications by Qiu et al [5]. Ongkodjojo and Tay reported a G-switch comprising an elastic beam for healthcare applications [6].…”
Section: Introductionmentioning
confidence: 99%